The association between the COVID-19 pandemic and interpersonal relationships among youth with a child maltreatment history - McCarthy, Julie-Anne; Osorio, Ana M.; Taillieu, Tamara L.; Stewart-Tufescu, Ashley; Afifi, Tracie O. (Frontiers in Child and Adolescent Psychiatry, 2024)
The COVID-19 pandemic had significant impacts on youth health and well-being. Youth with prior inequities, such as those exposed to child maltreatment, may have experienced greater psychosocial challenges and long-term difficulties than their peers, including sustained interpersonal relationships problems. Given the importance of healthy relationships during adolescence and early adulthood, the significant impact the pandemic had on youth, and the potential disproportionate challenges for youth with a child maltreatment history, the present study's purpose was to better understand changes in relational conflict among youth with and without a child maltreatment history from the perspectives of youth themselves. Specifically, the aims were to examine if youth child maltreatment history was associated with an increased likelihood of reporting increased conflict with a) parents, b) siblings, or c) intimate partners during the first three years of the COVID-19 pandemic. Data were drawn from the Well-Being and Experiences (WE) Study; a longitudinal and intergenerational cohort study of 1000 youth/parent dyads in Manitoba, Canada that began in 2017. WE study data were collected annually via self-reported youth surveys between 2017-2022 for a total of 5 waves of data collection, and COVID-19 questions were included in Waves 3 (2020), 4 (2021) and 5 (2022) (n=586, 56.43% female, ages 18 to 21 at Wave 5). Multinomial regressions models were computed to examine whether a youth's child maltreatment history was associated with increased, decreased, or consistent levels of conflict with parents, siblings, and intimate partners in 2020, 2021, and 2022 compared to pre-pandemic levels. Results indicated that compared to youth with no child maltreatment history, youth with a child maltreatment history were more likely to report increased conflict across all three types of relationships during first three years of the pandemic. Findings contribute to our understanding of the association between the COVID-19 pandemic and interpersonal relationships among youth who have a child maltreatment history compared to their peers without child maltreatment histories, signal potential long-term challenges or inequities for youth and families with a history of maltreatment, and may inform policy, programming, intervention, and recovery efforts in the post-COVID-19 period, and for future global emergencies.